2014
DOI: 10.4236/ajps.2014.53033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Methods on the Yield and Yield Attributes of Short Duration <i>Aman</i> Rice

Abstract: To find out the effect of planting methods on the yield and yield attributes of short duration Aman rice varieties, a field trial was conducted at the farm of Bangladesh Rice Research Institute, Gazipur, during July to November 2012. The treatments comprised of three BRRI released high yielding varieties viz., BRRI dhan39, BRRI dhan49 and BRRI dhan57 and three planting methods viz., direct seeding of dry seed, direct seeding of sprouted seed and transplanting. It was a factorial experiment conducted in a Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 5 publications
8
19
1
1
Order By: Relevance
“…Further, treatment dry direct sowing method (T 5 ) registered lowest gross, net and B: C ratio (Table 6). Similar finding was reported by Rana et al, (2014) higher B: C cost ratio under direct seeding of sprouted seed than transplanting methods due to saving of irrigation water and labour,…”
Section: Test Weight Yield Harvest Index and Economics Of Rice As Isupporting
confidence: 88%
“…Further, treatment dry direct sowing method (T 5 ) registered lowest gross, net and B: C ratio (Table 6). Similar finding was reported by Rana et al, (2014) higher B: C cost ratio under direct seeding of sprouted seed than transplanting methods due to saving of irrigation water and labour,…”
Section: Test Weight Yield Harvest Index and Economics Of Rice As Isupporting
confidence: 88%
“…While the main focus of the current work was on legume options, different rice possibilities were also examined in order to assess farm productivity. In the current experiments, cultivar BR49 took less time (9 to 13 d) to mature than in other reports (Rana et al 2014), with the difference presumably due to the use of older rice seedling (5 d) transplants in the current experiment and also different climatic conditions. However, long-duration rainfed monsoon rice cultivar BR49 produced higher yield than the short-duration rainfed monsoon rice cultivar BR33 and contributed to both higher REY and GEY from the cropping sequence with the control fallow period.…”
contrasting
confidence: 53%
“…The dry seeded rice had the opportunity to harvest 11 days earlier than transplanted rice which might reduce the application of supplemental irrigation in late planted Aman rice. Rana et al (2014) between dry direct-seeded rice and transplanted flooded rice which were consistent across different cultivars and years. On an average, dry direct-seeded rice produced 28.6 and 19.5 % more panicles m -2 than transplanted-flooded rice in 2012 and 2013, respectively.…”
Section: Review Of Literaturesupporting
confidence: 53%
“…As regard to yield attribute like number of grains panicle -1 Rana et al (2014) reported that the direct seeding of sprouted seed produced the highest number of total grains panicle −1 (151.357) while the lowest number of grains panicle −1 (132.446) was recorded from the direct seeding of dry seed method. Nourbakhshian et al (2000) and Yang et al (1998) found higher number of grains in sprouted seeds compared to that transplanting.…”
Section: Review Of Literaturementioning
confidence: 99%